2019
DOI: 10.2754/avb201988020129
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of glutathione concentration in whole blood of Holstein dairy calves

Abstract: The aim of this study was to evaluate the concentrations of total (T-GSH), oxidized (GSSG) and reduced glutathione (GSH) in blood of clinically healthy calves, to assess the effect of sex and age together with the type of feeding on its concentrations, and to assess the relationships between glutathione and metabolic indices. A total of 117 Holstein calves at the age of 1 day to 6 months were divided according to age and together with the type of feeding into 4 groups: colostrum and transition milk (n = 20), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…38 Specifically, gentle agitation in the absence of GSH, which was used to mimic the potential structural disturbance of MAWI coacervate due to moving or flushing of body fluids like blood, caused only about 10% leakage of encapsulated 3T3 mouse embryonic fibroblast cells or bovine serum albumin (BSA) after 2 h. In contrast, elevation of GSH concentration to 10 mM during gentle agitation induced accelerated structural degradation and therefore release of most cargoes encapsulated within the MAWI coacervate robot. Compared with 10 mM GSH, 0.5 mM GSH, the physiological concentration in serum, 39 led to more prolonged coacervate degradation and sustained release of loaded cargoes, thus potentially providing the coacervate robot with enough time to reach the targeted intravascular position for in situ cargo release.…”
mentioning
confidence: 99%
“…38 Specifically, gentle agitation in the absence of GSH, which was used to mimic the potential structural disturbance of MAWI coacervate due to moving or flushing of body fluids like blood, caused only about 10% leakage of encapsulated 3T3 mouse embryonic fibroblast cells or bovine serum albumin (BSA) after 2 h. In contrast, elevation of GSH concentration to 10 mM during gentle agitation induced accelerated structural degradation and therefore release of most cargoes encapsulated within the MAWI coacervate robot. Compared with 10 mM GSH, 0.5 mM GSH, the physiological concentration in serum, 39 led to more prolonged coacervate degradation and sustained release of loaded cargoes, thus potentially providing the coacervate robot with enough time to reach the targeted intravascular position for in situ cargo release.…”
mentioning
confidence: 99%
“…Exposing animals to stress compromises their welfare. Various studies have focused on the assessment of stress and welfare in farm animals (Nečasová et al 2019;Píšťková et al 2019;Večerková et al 2019;Večerek et al 2020Večerek et al , 2021. Increasing summer temperatures present one of the stressors for livestock (Autukaite et al 2020).…”
mentioning
confidence: 99%
“…Moreover, the increased incidence of disease during the periparturient period is directly related to numerous genetic, physiological and environmental factors that can compromise the cow's immunological defences (Sordillo 2005). Necasova et al (2019) found a significant effect of the age together with the type of feeding of calves on the concentration of GSSG and the GSH/GSSG ratio. Calves fed colostrum, transition or native milk showed an increase in the GSSG levels compared to calves receiving milk replacer and calves after weaning.…”
mentioning
confidence: 99%